INTEGRASI NILAI-NILAI KEISLAMAN DALAM KURIKULUM DAN PERKULIAHAN PROGRAM STUDI TADRIS BIOLOGI - Nanik Lestariningsih; Yatin Mulyono; Ayatusa'adah Ayatusa'adah (IAIN Palangka Raya, 2017)
This study aims to see the integration of values in the curriculum and lectures in biological tadris/departement study program using a qualitative approach. This type of research is divided into two, namely the type of content analisys research and the type of field research research. Types of content analisys research using curriculum data, while the lecture process taken samples in the Higher Botanical Botanical field using field research. The research data was collected through survey, interview, and document analysis. The results show that the application of the integration of Islamic values contained in the curriculum book uses a model of developing an educational curriculum in educational institutions, in which there is integration in the graduation profile, the main competencies of graduates, and additional or other competencies. The results of research indicate that the study of the High Botanical Botanical course uses an integration model to explore the verses in the Qur'an and the methodological integration model by implementing the Islamic integration on the process as well as the evaluation. Application of lectures and lab activities in the laboratory with a methodological integration model. The integration contained in the RPS document contains Islamic values by listing the suras and verses in the Qur'an.